Characterization of a novel l-phenylalanine oxidase from Coprinopsis cinereus and its application for enzymatic production of phenylpyruvic acid. (October 2017) - Zhang, Jianzhi; Yang, Dong; Yan, Qiaojuan; Jiang, Zhengqiang
Graphical abstract: Highlights: Heterologous expression ofl -phenylalanine oxidase from mushroom Coprinus cinereus . The enzyme exhibited specific activity towards phenylalanine over other 19 amino acids. Resolution of racemic ofnull, l -phenylalanine mixture by the enzyme. The enzyme exhibited higher enzymatic activity, and phenylpyruvic acid titer. Abstract: A novell -phenylalanine oxidase gene from a species of mushroom Coprinopsis cinereus was cloned. Withl -amino acid oxidase from Hebeloma cylindrosporum, which is the closest one, it shared only 30.6% sequence identity. This recombinant protein was expressed in Escherichia coli, purified and biochemically characterized. It contained 778 amino acids and was quite different compared with all previously studied enzymes. This enzyme exhibited highest specific activity of 6.04 U/mg towardsl -phenylalanine and the optimal pH, temperature of the enzyme catalyzed reaction were 8.5 and 45 °C. The enzyme was stable up to 55 °C within pH range 7.0–9.5. It could oxidizel -phenylalanine to phenylpyruvic acid at high titer (8.1 ± 0.1 g/L), conversion ratio (97.4 ± 0.2%) and productivity (1.02 ± 0.01 g/L h) within 8 h. More importantly, it specifically catalyzed the oxidation ofl -phenylalanine with racemicnull, l -phenylalanine mixture as substrate. In general, these properties rendered it a useful catalyst in several industrial manufacturers.